Sains-du-Nord (Nord) : une agglomération de la cité des Nerviens - Pascal Neaud (Gallia)
The ancient agglomeration of Sains-du-Nord (Nord) is known thanks to casual discoveries made since the 19th c. from the end of the 20th c., thanks to the development of rescue archaeology, new vestiges have been excavated, sometimes on large areas. In spite of difficult contexts of intervention (reduced deadlines and sites partially destroyed by the building of new constructions), these operations contributed to increase our knowledge about this ancient settlement, which has been, from then on, characterised as a small town. After ten years of interruption, six new archaeological operations were led on the site. They opened the study of various contexts relating to the religious, domestic and craft fields. Therefore, those new datas allowed to enrich and to renew our perception of this agglomeration. On these bases, we can now propose a first topographical approach of this ancient site, as well as an hypothesis about its origins.